Affective and reflective attitudes toward vegetarian food consumption: the effect of goal priming - Daiss, Fabian; Jansen, Petra (Frontiers in Nutrition, 2025)
ObjectivesThe study’s primary goal was to investigate the effect of goal priming on implicit and explicit attitudes toward vegetarian food consumption and food choice behavior within the context of dual-process models that describe sustainable behavior.MethodsA total of 128 participants were randomly assigned to either a goal priming intervention group or a control group. After reading a short priming text, all participants completed an explicit rating task, an Implicit Association Test (IAT), and a simulated online supermarket task to assess actual food-related choices.ResultsParticipants in the intervention group exhibited significantly more positive implicit attitudes toward vegetarian food compared to those in the control group. Explicit attitudes toward vegetarian food were also significantly more positive in the intervention group, although to a smaller extent. No significant group differences were found in explicit attitudes toward meat-based nutrition or in food choice behavior. However, mediation analysis revealed a significant indirect effect of goal priming on behavior via implicit attitudes. Exploratory analyses showed consistent gender differences across all outcome variables, which attenuated the priming effects when included as a covariate.ConclusionAlthough the intervention did not result in direct behavioral change, the findings support the potential of goal priming to influence automatic affective and reflective processes that may precede the development of sustainable behavior.